Mexico : - King, Timothy (The Development Centre of the Organization for Economic Co-operation and Development by Oxford University Press, 1970)
Contents: The Industrialization of Mexico before 1940; Economic Development since 1940; The Overall Policy Framework; The Instrument of Industrialization Policy; Economic Analysis of Policy Instruments Affecting the Pattern of Industrialization; The Outcome of Policy...